Frontiers in applied general equilibrium modeling : in honor of Herbert Scarf - Kehoe, Timothy Jerome, 1953-; Srinivasan, T. N., 1933-2018; Whalley, John (Cambridge University Press, 2005)
This volume brings together twelve papers by many of the most prominent applied general equilibrium modelers honoring Herbert Scarf, the father of equilibrium computation in economics. It deals with new developments in applied general equilibrium, a field which has broadened greatly since the 1980s. The contributors discuss some traditional as well as some newer topics in the field, including non-convexities in economy-wide models, tax policy, developmental modeling and energy modeling. The book also covers a range of new approaches, conceptual issues and computational algorithms, such as calibration and new areas of application such as macroeconomics of real business cycles and finance. An introductory chapter written by the editors maps out issues and scenarios for the future evolution of applied general equilibrium.